Vernacular Creativity and a New Media: Istockphoto - Yengin, Deniz; Ekim, Berna (The Turkish Online Journal of Design, Art and Communication, 2011)
Globalization or McLuhan’s “Global Village” concept is increasingly getting a clearest shape. Along with globalization, communication mediums are also developing. They have the qualities of being digital, interactive, and virtual and are thus “new” mediums of communication. Due to these qualities, communication mediums are changing form and are being used by network societies. These mediums also influence individual creativity due to their interactive use. Individuals can create and share their own visual designs, especially when employing social networks. Creativity differs from person to person, as it does from region to region. In this study, visual designs created with new media will be examined and the concept of vernacular creativity will be defined and explained. The social network istockphoto will be used as an example for analysis. According to this example, this study will be delivered with qualitative and quantitative methods.
Keywords: Vernacular Creativity; New Media; Social Network; Network Society; Interaction; Digitalization; Virtuality; Istockphoto; Argo Yaratıcılık; Yeni Medya; Sosyal Ağ; Ağ Toplumu; Etkileşim; Dijitalleştirme; Sanallık